Managing Swedish Newspapers in the Digital Age An Investigation of Managerial Responsibility and Innovation - Niculescu,Roxana (2016)
The whole word has been getting somewhat familiar with the crisis that the newspaper industry has been experiencing. The past decade has seen print mainly absorbing finances with little to no profits, and the ever-growing digital not offering enough advertising revenue. Hence, the challenges managers face becomes clear: how can we innovate effectively when the current system is a loophole? Additionally, how willing are we to take risks in a completely traditional environment? The attempt to answer these questions entails the overview of the industry, as well as two representative examples of local newspapers in Sweden: Sydsvenskan and Skånska Dagbladet. By discussing these issues with contacts highly relevant to the industry, this report aims at better understanding the extents to which newspapers’ management are responsible for the lack of innovations in a digital world. Another aim is to grasp the reality of more than one challenge they face. Herein, digitalization plays an essential role in the research due to how it has been challenging the traditional business model of newspaper organizations. Subsequently, the study encompasses the following challenges for the industry: the traditional business model, the management roles in newspaper companies, and the implications of digitalization for the present and future of the industry. Together with the theoretical framework, the study’s results come from a combination of interviews, necessary data, and other empirical studies that altogether form the empirical material of this report. Furthermore, in identifying and discussing the challenges of the traditional business, the separate cases of local players contrasted with national/international players, as well as the role of management in innovating, the report’s primary finding and possible solution is for managers to consider stirring their organizations towards an ambidextrous structure: integrating what is useful about the past, yet focusing on creating current actions for a more hopeful future.
Keywords: newspapers; management; newspaper industry; swedish newspapers; innovation challenges; digitalization; ambidextrous organization; traditional business model; management roles; local newspapers; international newspapers.